2024
DOI: 10.1002/aenm.202304331
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Powered Multiphase Flow Detection Through Triboelectric Nanogenerator‐Based Displacement Current

Wenlong Ma,
Peng Wang,
Baofeng Zhang
et al.

Abstract: Accurate measurement of complicated multiphase flow is crucial to the safety and efficiency of petroleum and chemical industrial facilities. However, the existing multiphase flow detection techniques are not applicable to pipelines in remote regions including deserts or deep seas, due to the high cost of providing a stable power supply. Herein, a self‐powered multiphase flow sensor, composed of a liquid‐driven triboelectric nanogenerator (TENG) ‐based signal generator, a ring‐type transmitter, and a string‐typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Ma et al 93 observed that increasing temperature has a negative impact and the extreme acidity or alkalinity has a positive impact on the overall output. A self-powered multiphase flow sensor was proposed, which accurately reflects the wetting state inside a pipeline, capable of distinguishing between static water and air phases.…”
Section: Factors Affecting the Efficiency Of F-tengsmentioning
confidence: 99%
“…Ma et al 93 observed that increasing temperature has a negative impact and the extreme acidity or alkalinity has a positive impact on the overall output. A self-powered multiphase flow sensor was proposed, which accurately reflects the wetting state inside a pipeline, capable of distinguishing between static water and air phases.…”
Section: Factors Affecting the Efficiency Of F-tengsmentioning
confidence: 99%